Deformation fabrics and strain localization mechanisms in graphitic carbon-bearing rocks from the Ailaoshan-Red River strike-slip fault zone. (November 2020) - Lyu, Meixia; Cao, Shuyun; Neubauer, Franz; Li, Junyu; Cheng, Xuemei
Abstract: Graphitic carbon-bearing rocks generally occur in low-to high-grade metamorphic units. In many brittle faults, graphitic carbon is often associated with gouge or low-grade metamorphic rocks whereas in ductile faults, graphitic carbon commonly occurs in marble, schist or gneiss. Carbonaceous material gradually transforms from an amorphous into an ordered crystalline structure by increasing thermal metamorphism. The degree of graphitization is believed to be a reliable indicator of peak temperature conditions in the metamorphic rock. In this contribution, based on detailed field observations, the variably deformed and metamorphosed graphitic gneisses to phyllites, located within the footwall and hangingwall unit of the Cenozoic Ailaoshan-Red River strike-slip shear zone are studied. According to lithological features and temperatures determined by Raman spectra of carbonaceous material, these graphitic rocks and deformation fabrics are divided into three types. Type I is represented by medium-grade metamorphism and strongly deformed rocks with an average temperature of 509 °C and a maximum temperature of 604 °C. Type II is affected by low-grade metamorphism and deformed rocks with an average temperature of 420 °C. Type III is affected by lower-grade metamorphism and occurs in weakly deformed/undeformed rocks with an average temperature of 350 °C. Slip-localized micro-shear zones and laterally continuous or discontinuous slip-planes constituted by graphitic carbon aggregates are developed in Types I and II. The electron back-scattered diffraction (EBSD) lattice preferred orientation (LPO) patterns of graphitic carbon grains were firstly observed in comparison with LPO patterns of quartz and switch from basal, rhomb to prism slip systems, which indicate increasing deformation temperatures. Comparison of quartz and graphite LPOs indicates that graphite LPOs show higher temperature conditions. According to the graphitic slip-planes, micro-shear zones with grain-size reduction and mylonitic foliation constituted by graphitic carbon minerals, we also propose that the development of fine-grained amorphous carbon plays an important role in rheological weakening of the whole rock during progressive ductile shearing. Highlights: Fabric characterisation of three types of variably deformed and metamorphosed graphitic carbon-bearing rocks. Graphite Lattice Preferred Orientations firstly observed as same patterns of quartz a switch from basal to prism slip. Graphite slip systems indicate increasing metamorphism and deformation temperatures. Graphitic carbon micro-shear zone and shear plane plays an important role in rheological weakening in natural fault zone.